Model kematian biota air sebagai fungsi waktu kontak pada air limbah deterjen dan gagasan sederhana pengendaliannya - Yuliya Mahdalena Hidayat (JURNAL SUMBER DAYA AIR, 2016)
Wastewater is a residual from detergents usage that has negative impact to the environment, such as aquatic biota toxid. The Model of aquatic biota mortality as a function of detention time for the wastewater detergent concentration was eliminated by secondary data. Model is selected by election of trendline type that have highest determination coefficient, while simple idea of the detergent pollution control technique was analized from previous research and some other aspect. Result showed that aquatic biota mortality with perception time can be expressed with second order polynominal model. Damage of the vital aquatic biota organ such as cell membran, liver and heart, and also water quality degradation is allegedly caused of organisms mortality as a due to detergent increased in water bodies. A very high detergent concentration, is endangering biota in water bodies. Usage of environmentally friendy detergens, and also wastewater treatment for detergent before entering the water bodies, is expected to protecting more aquatic biota so that ecosystem can maintained. Individual detergent screening technique (TPDI) idea expected acceptable and exploted by public as one of the detergent pollution control.